Analysis of the Mathematical Connection Ability of Development Economics Students in Solving Row and Series Problems - Uyun, Musmiratul (Jurnal Ilmiah Mandala Education (JIME), 2026)
Mathematics plays a crucial role in developing students' logical, analytical, and systematic thinking skills, including in the discipline of Development Economics. One important aspect of mathematics is mathematical connections, namely the ability to connect mathematical concepts across topics, with other disciplines, and with real-world contexts. As one of the abilities in mathematics, connection skills must be cultivated in students. Therefore, it is necessary to conduct a study entitled Analysis of Mathematical Connection Skills of Development Economics Students in Solving Sequence and Series Problems. The research was conducted in the Development Economics study program, Faculty of Economics and Business, Al-Azhar Islamic University. The objects of this study were 32 second-semester students. The type of research used was qualitative research. The results of this study obtained an average percentage of mathematical connection skills of 77.2%, which means that almost all students in the Development Economics study program have moderate mathematical connection skills.